Significant efficacy and well safety of apatinib combined with radiotherapy in NSCLC: Case report. Issue 50 (December 2017) - Zhao, Chunbo; Zhang, Qian; Qiao, Wenbo
Abstract: Rationale: The outcomes of locally advanced non-small cell lung cancer (NSCLC) remain poor, in particular, the frail elderly patients cannot tolerate chemotherapy. The new efficient, safe, and more specific treatments are needed. Radiation combined with targeted therapy is the focus of research in recent years. Apatinib is highly selective tyrosine kinase inhibitor of vascular endothelial growth factor receptor-2, studies have revealed that apatinib inhibit the growth of solid tumors including NSCLC. However, there is no report to evaluate its efficacy and safety in combined with radiotherapy for the advanced NSCLC. Our original research about to explore the use of apatinib combined with radiotherapy in treatment of NSCLC and its side effects are as follows. Patient concerns: Patient 1, man, 78-year old, admitted to hospital, due to "thoracalgia and dyspnea for 1 month." Chest and abdomen computed tomography (CT) scan showed that there was a huge mass at the left upper lobe and multiple lymph nodes metastasis in mediastinum and left hilus pulmonis, the diagnosis was left lung squamous cell carcinoma, however, the mass was huge and age of patient was elder, post chemotherapy the mass were bigger and more severe. Patient 2, man, 61-year old, the diagnosis was squamous carcinoma on left upper lobe with right mediastinum lymph notes metastases recrudescence post chemoradiotherapy. Diagnoses: Case 1 was diagnosed left lung huge squamous cell carcinoma and case 2 was left lung squamous carcinoma, the primary lesion and right mediastinum lymph notes metastases recrudescence after radiochemotherapy. Interventions: Both patients who received local radiation therapy and concurrent apatinib. Apatinib 250 mg once daily in combination with thoracic radiotherapy (2 Gy/d, 5 fractions/wk) followed by Apatinib Maintenance Therapy. Outcomes: Favorable oncologic outcomes were achieved in the 2 cases after the treatment. The common side effects of apatinib were hypertension and hand-foot syndrome; however, the toxicity of was controllable and tolerable, no dyspnea, no hemoptysis, no thoracalgia. Lessons: Apatinib combined with thoracic radiotherapy, may be an option for recurring or advanced NSCLC. But that still warrants further investigation in the prospective study.